การพัฒนากระบวนการถ่ายทอดเทคโนโลยีเพื่อเพิ่มประสิทธิภาพ ของระบบการขนส่งทางอากาศไทย - สันธนาภรณ์ สุจิตรา; สิรสุนทร พัชรินทร์; ปัทมสิริวัฒน์ ดิเรก (วารสารวิชาการ มหาวิทยาลัยราชภัฏอุตรดิตถ์, 2016)
วัตถุประสงค์การวิจัย เพื่อวิเคราะห์การถ่ายทอดเทคโนโลยีการขนส่งทางอากาศของประเทศไทย หน่วยวิเคราะห์ คือ สายการบิน ท่าอากาศยาน และการควบคุมจราจรทางอากาศ โดยสันนิษฐานว่ามีความตระหนักรู้ด้านเทคโนโลยีที่เป็นมิตรต่อสิ่งแวดล้อม และแนวทางแก้ไขปัญหามลพิษของแต่ละหน่วยงาน โดยสัมภาษณ์เชิงลึกผู้ประกอบการ 101 ราย และองค์กรด้านนโยบายและกำกับดูแล 22 ราย ใช้วิธีการสามเส้า (Triangulation) เพื่อตรวจสอบความแม่นยำของเนื้อหา ผลการวิจัยพบว่า 1) ความสามารถในการถ่ายทอดเทคโนโลยีในอุตสาหกรรมการบินโดยรวมอยู่ในระดับจัดหาและใช้เทคโนโลยี จากการวิเคราะห์การถดถอยเชิงพหุ พบว่า ปัจจัยสำคัญที่มีผลต่อการถ่ายทอดเทคโนโลยีทั้งสองระดับเป็นปัจจัยในกลุ่มคุณลักษณะขององค์กร ที่น่าสนใจ ได้แก่ ความตระหนักรู้ ผลประกอบการ และขนาดองค์กร อย่างไรก็ตามความสามารถในการถ่ายทอดเทคโนโลยีในระดับที่สูงขึ้นทั้งการดัดแปลงเทคโนโลยี และสร้างนวัตกรรม โดยรวมยังมีอยู่ค่อนข้างน้อย ซึ่งปัจจัยที่มีผลต่อความสามารถทางเทคโนโลยีในขั้นสูงขึ้น ได้แก่ ปัจจัยในกลุ่มความสัมพันธ์เชิงสถาบัน คือ มาตรการส่งเสริม รวมถึงช่องทางการถ่ายทอด และเมื่อวิเคราะห์ด้วยวิธีการสามเส้าให้ผลที่สอดคล้องกัน 2) กระบวนการถ่ายทอดเทคโนโลยีการบินที่เป็นมิตรกับสิ่งแวดล้อมมีการดำเนินการเชิงพลวัตใน 9 ขั้นตอน มีปัญหาสำคัญ ได้แก่ ความล่าช้าและยกเลิกการดำเนินงานซึ่งส่วนใหญ่อยู่ในขั้นตอนต้นและท้ายของกระบวนการ รวมทั้งการเผชิญกับความขัดแย้งในการตัดสินใจระหว่างการดำเนินกระบวนการ ถึงการเลือกตอบโจทย์ระหว่างมิติเศรษฐกิจ สังคม สิ่งแวดล้อมภายใต้กรอบความยั่งยืน เพื่อพัฒนากระบวนการถ่ายทอดให้มีประสิทธิภาพเพิ่มขึ้นโดยปรับลดขั้นตอนให้เหลือ 7 ขั้น โดยมีบางขั้นที่ดำเนินการพร้อมกันในลักษณะคู่ขนานได้ และเพิ่มขั้นตอนวิจัยพัฒนาและทดสอบระบบ และขั้นปรับเทคโนโลยีให้เข้ากับสภาพองค์กร รวมทั้งเสนอแนวทางเลือกว่า สามารถยกระดับความสามารถทางเทคโนโลยีให้สูงขึ้นโดยให้ความสำคัญกับวิจัยและพัฒนาเทคโนโลยี รวมทั้งให้ความสำคัญเงื่อนไขสำคัญในการไปต่อขั้นต่อไปหรือยกเลิกการดำเนินงานระหว่างกระบวนการ ปัจจัยที่มีอิทธิพลร่วมกันหลายขั้นตอน ที่สำคัญคือ ความตระหนักรู้ ช่องทางการถ่ายทอด ความสามารถทางเทคโนโลยี ความร่วมมือกันระหว่าง และงบประมาณ 3) มาตรการส่งเสริมกระบวนการถ่ายทอดเทคโนโลยีที่ใช้ในปัจจุบันส่วนใหญ่อยู่ในกลุ่มสั่งการและควบคุม ขณะที่มาตรการกลุ่มใหม่ๆ เช่น กลุ่มเศรษฐศาสตร์ กลุ่มสร้างแรงจูงใจ ยังมีการใช้ค่อนข้างน้อย มาตรการส่งเสริมยังคงมีผลต่อการปรับพฤติกรรมผู้ประกอบการได้ไม่ มากนัก เพื่อให้เครื่องมือส่งเสริมให้กระบวนการถ่ายทอดเทคโนโลยีมีประสิทธิภาพเพิ่มขึ้น ควรใช้มาตรการหลายกลุ่มร่วมกัน และให้ความสำคัญกับการปรับกระบวนทัศน์จากการกำกับดูแลมาสู่การให้ความร่วมมือระหว่างรัฐกับเอกชน The Development of Technology Transfer Process for Increasing Effectiveness of Thai Aviation System The objective of this study was to analyze the technology transfer to the Thai aviation system. The analysis incorporates airports, air traffic control and airlines. This study hypothesized that there is awareness on environmentally friendly technology and the solution of existing and upcoming problems in each agency. For the analysis of the technology transfer, in-depth interviews were conducted with 22 corporate governance departments/officials and regulators who were responsible for policies and regulations, and with 101 operators. A triangulation method was utilized to check the accuracy of the contents. The following results are derived from the analysis of this research: 1) The ability to transfer technology in the aviation industry is observed as a whole in the acquisitive and operative capability levels. A multiple regression analysis postulates that the key factors affecting the transfer of technology are both the enterprise features and interest of concerned persons including their awareness of environmental technology transfer to aviation system. However, the ability to transfer technology to a higher levels of adaptation and innovations are quite a few overall . The factors that affect advanced technological capabilities depend upon promotion of institutional relational measures. The analysis of broadcast channel shows that they provide consistent results with the centers. 2) The transfer of environmentally friendly aerospace technology depends upon dynamic action in the nine stages in the process, which are crucial to the problems and delays in the transfer of environmental friendly technologies to aviation system. The discontinued operation is the earliest stage and dealing with conflict is the last stage in the process. The economic and social dimensions are also to be more considered in choosing the appropriate technology while making the decisions during the implementation process than environmental dimension. This research has come up with a Sustainability Framework to improve the process of technology transfer more effectively by reducing the aforementioned nine steps to seven steps. There are some steps that perform simultaneously in parallel, such as research, development and testing procedures. The leverage to existing technology is giving priority to research and development of technology. Advanced technologies and their adaption depend upon conditions of the organization, including the proposed technology choice. The crucial importance of going to the next step or terminate the process depend upon factors that share many important steps include awareness, broadcast channel, technological capability, cooperation, and budget. 3) Currently, the major measure used to promote the transfer of technology is the group command and control. There is relatively little use of incentive measures which affect the behavior of the operators. To properly promote the transfer of technology more effectively several measures should be grouped together, and the focus should be given to the paradigm of governance with better coordination and cooperation among and between the state and private sectors.